S. Montero, G. Bravo, J. Martínez-Pinna: El Imperio Romano. Evolución institucional e ideológica. Madrid, Visor, 1991. 482 + 3 mapas. - BLÁZQUEZ, J. M. (Gerión. Revista de Historia Antigua, 1992)
Sin resumen